2022
DOI: 10.1111/imcb.12521
|View full text |Cite
|
Sign up to set email alerts
|

ZC3H12C expression in dendritic cells is necessary to prevent lymphadenopathy of skin‐draining lymph nodes

Abstract: The role of RNA-binding proteins of the CCCH-containing family in regulating proinflammatory cytokine production and inflammation is increasingly recognized. We have identified ZC3H12C (Regnase-3) as a potential post-transcriptional regulator of tumor necrosis factor expression and have investigated its role in vivo by generating Zc3h12c-deficient mice that express green fluorescent protein instead of ZC3H12C. Zc3h12c-deficient mice develop hypertrophic lymph nodes. In the immune system, ZC3H12C expression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…and Langerhans cells) in the lymph nodes, and when genetically deleted from mice, the absence of this RNAbinding protein led to lymphadenopathy. 4 Interestingly, deficiency in TNF-a reversed the effect suggesting a regulatory role for ZC3H12C on TNF-a especially during skin homeostasis. 4 Curson et al 5 investigated a newly identified variant of Scimp, an adapter in TLR signaling, to discover that its unique signaling and localization supported distinct and diverse functions through this key innate signaling pathway in macrophages.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…and Langerhans cells) in the lymph nodes, and when genetically deleted from mice, the absence of this RNAbinding protein led to lymphadenopathy. 4 Interestingly, deficiency in TNF-a reversed the effect suggesting a regulatory role for ZC3H12C on TNF-a especially during skin homeostasis. 4 Curson et al 5 investigated a newly identified variant of Scimp, an adapter in TLR signaling, to discover that its unique signaling and localization supported distinct and diverse functions through this key innate signaling pathway in macrophages.…”
mentioning
confidence: 98%
“…• Clayer et al 4 ZC3H12C expression in dendritic cells is necessary to prevent lymphadenopathy of skin-draining lymph nodes.…”
mentioning
confidence: 99%
See 3 more Smart Citations